Is contextualised admission the answer to the access challenge?. (1st October 2016) - Mountford-Zimdars, Anna; Moore, Joanne; Graham, Janet
ABSTRACT: This article reviews the idea of contextualising applicants to higher education in order to widen access. First, the meaning of contextualised admissions (CAs) is discussed before laying out the rationale for contextualising applicants and the beneficiaries of the policy. The final sections discuss key critiques of CA and conclude by arguing that CA does go some way to addressing the access challenge. To fully realise its potential as a policy intervention though, it is most helpfully part of integrated support for students throughout university and is mindful of the role of universities in wider society to create more equal progression trajectories for young people from a range of backgrounds.